Haemostatic Factors and Inhibitors and Coronary Artery Bypass Grafting: Preoperative Alterations and Relations to Graft Occlusion - Moor, Elisabeth; Hamsten, Anders; Blombäck, Margareta; Herzfeld, Istvan; Wiman, Björn; Rydén, Lars (Thrombosis and Haemostasis, 1994)
Graft closure remains a major problem after coronary artery bypass surgery. While a number of graft characteristics influencing the risk of occlusion have been defined, the role of haemostatic factors and inhibitors has not been studied in detail. The present study examined the time course of changes in blood coagulation and fibrinolytic function after coronary artery bypass grafting in 20 consecutive patients. Pre- and postoperative determinations of haemostatic factors and inhibitors were also related to the presence of graft occlusion assessed by angiography at three months after surgery. A broad panel of haemostatic tests was used preoperatively, on the first, third and eight postoperative days, and at three months after surgery. A particular emphasis was placed on fibrinogen, factor VII activity, von Willebrand factor (vWF), plasminogen activator inhibitor-1 (PAI-1) activity, anticoagulant proteins C and S, thrombin-antithrombin complex and D-dimer. A marked activation of the coagulation cascade was noted postoperatively along with enhanced degradation of cross-linked fibrin. The degree of activation of blood coagulation and fibrinolysis differed widely between individuals and appeared to relate only partly to the acute phase reaction produced by the surgical trauma. Preoperative values of haemostatic factors and inhibitors showed fairly weak associations with the levels of postoperative determinations. Basal tPA and factor VIII levels, fibrinogen and TAT concentrations on the third and eighth postoperative day, and factor VII amidolytic activity on the third postoperative day differed (p <0.05) between patients with and without occluded grafts at reangiography. Accordingly, combined pre- and postoperative assessment of haemostatic function may contribute to the identification of individuals at risk for early graft closure after coronary artery bypass grafting.